Exploration of the Potential Mechanism of Yujin Powder Treating Dampness-heat Diarrhea by Integrating UPLC-MS/MS and Network Pharmacology Prediction - Jiang, Li-dong; Zhang, Wang-dong; Wang, Bao-shan; Cai, Yan-zi; Qin, Xue; Zhao, Wen-bo; Ji, Peng; Yuan, Zi-wen; Wei, Yan-ming; Yao, Wan-ling (Combinatorial Chemistry & High Throughput Screening, 2024)
Background: Yujin powder (YJP) is a classic prescription for treating dampness-heat diarrhea (DHD) in Traditional Chinese Medicine (TCM), but the main functional active ingredients and the exact mechanisms have not been systematically studied. Objectives: This study aimed to preliminarily explore the potential mechanisms of YJP for treating DHD by integrating UPLC-MS/MS and network pharmacology methods. Methods: Ultra performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) technology was used to determine the ingredients of YJP. And then, the targets of these components were predicted and screened from TCMSP, SwissTargetPrediction databases. The disease targets related to DHD were obtained by using the databases of GeneCards, OMIM, DisGeNET, TTD, and DrugBank. The protein-protein interaction networks (PPI) of YJP-DHD were constructed using the STRING database and Origin 2022 software to identify the cross-targets by screening the core-acting targets and a network diagram by Cytoscape 3.8.2 software was also constructed. Metascape database was used for performing GO and KEGG enrichment anlysis on the core genes. Finally, molecular docking was used to verify the results with AutoDock 4.2.6, AutoDock Tools 1.5.6, PyMOL 2.4.0, and Open Babel 2.3.2 software. Results: 597 components in YJP were detected, and 153 active components were obtained through database screening, among them the key active ingredients include coptisine, berberine, baicalein, etc. There were 362 targets treating DHD, among them the core targets included TNF, IL-6, ALB, etc. The enriched KEGG pathways mainly involve PI3K-Akt, TNF, MAPK, etc. Molecular docking results showed that coptisine, berberine, baicalein, etc., had a strong affinity with TNF, IL-6, and MAPK14. Therefore, TNF, IL-6, MAPK14, ALB, etc., are the key targets of the active ingredients of YJP coptisine, baicalein, and berberine, etc. They have the potential to regulate PI3K-Akt, MAPK, and TNF signalling pathways. The component-target-disease network diagram revealed that YJP treated DHD through the effects of anti-inflammation, anti-diarrhea, immunoregulation, and improving intestinal mucosal injury. Conclusion: It is demonstrated that YJP treats DHD mainly through the main active ingredients coptisine, berberine, baicalein, etc. comprehensively exerting the effects of anti-inflammation, anti-diarrhea, immunoregulation, and improving intestinal mucosal injury, which will provide evidence for further in-depth studying the mechanism of YJP treating DHD.
Keywords: PPI